ENVIRONMENTAL PROTECTION ACT - Vincent, Kamlini; Khatri, Amrita (International Journal of Research -GRANTHAALAYAH, 2015)
It is not as though degradation of environment is only a recent phenomenon. In the past also human activities have resulted in the degradation of environment, though they were not aware of it. Mans impact on the environment has resulted in pollution of environment. The protection and improvement of the human environment is a major issue which affects the well-being of people and economic development. Environmental protection is a practice of protecting the environment, on organizational levels, for the benefit of the natural environment and human- been. According to section 2 (a) of the environmental protection Act, ‘Environment’ includes water, air and land inter-relationship which exists among and between water, air and land and human beings other living creatures, plants, micro-organism and property. There are about two hundred laws dealing with environmental protection both before and after independence in India.